2006
DOI: 10.1002/app.24706
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of alginate and hydroxyapatite‐based biocomposite

Abstract: In this article, we report a novel route for the preparation of alginate‐hydroxyapatite biocomposite. Hydroxyapatite has been nucleated on alginate chains by precipitation method to obtain a biomimetic artificial bone‐like composite. The composite was characterized by powder XRD, FTIR, TGA, DTA, and SEM to ascertain its phase homogeneity and particle size distribution. Hydroxyapatite particles on alginate matrix are around 500–1000 nm in diameter. © 2006 Wiley Periodicals, Inc. J Appl Polym Sci 102: 5162–5165,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 25 publications
3
37
0
Order By: Relevance
“…Besides the previously mentioned collagen, a wide variety of natural polymers have been involved in the synthesis of bio-nanohybrid materials with potential application in bone repair and dental prostheses. For instance, some recent examples refer to bionanocomposites based on the combination of HAP with alginate [96,97], chitosan [98,99], bovine serum albumin (BSA) [100], sodium caseinate [101], hyaluronic acid [102], silk fibroin [103,104], silk sericin [105], or polylactic acid (PLA) [106,107]. These examples illustrate the increasing interest in the subject of HAP-based biohybrid materials, which has led to almost 400 articles appeared in scientific journals in 2006 alone.…”
Section: Calcium Phosphates and Carbonates In Bioinspired And Biomimementioning
confidence: 99%
“…Besides the previously mentioned collagen, a wide variety of natural polymers have been involved in the synthesis of bio-nanohybrid materials with potential application in bone repair and dental prostheses. For instance, some recent examples refer to bionanocomposites based on the combination of HAP with alginate [96,97], chitosan [98,99], bovine serum albumin (BSA) [100], sodium caseinate [101], hyaluronic acid [102], silk fibroin [103,104], silk sericin [105], or polylactic acid (PLA) [106,107]. These examples illustrate the increasing interest in the subject of HAP-based biohybrid materials, which has led to almost 400 articles appeared in scientific journals in 2006 alone.…”
Section: Calcium Phosphates and Carbonates In Bioinspired And Biomimementioning
confidence: 99%
“…15,16 Hydroxyapatite (HA, Ca 10 (PO 4 ) 5 (OH) 2 ), which is a major inorganic component of bone, has been widely used in the orthopedic and dental fields as pastes, granules, or porous blocks for implants. 17 HA and natural polymers, such as collagen, 18 gelatin, 19 alginate, 20 and CS 21,22 composite materials have been extensively investigated. It was reported that the introduction of HA could improve the activ-ity and viability of cells cultured on composites, 23 or improve both the mechanical and cell-attachment properties of the alginate scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…These processes are followed by fragments and monomer units conversion into carbonate as a by-product. Finally due to oxidation of the carbonate, endothermic peak with minimum at 817 o C and mass loss of ~6% was occurred in the temperature interval form 700 to 1000 o C [16,17]. From Figure 1 it is clear that processes occurred in the temperature interval from 180 to 700 o C are exothermic, indicating that energy released from burning or forming new chemical bonds was greater than the energy absorbed for bond scission during decomposition.…”
Section: Methodsmentioning
confidence: 98%